Chinese Cultural Diplomacy towards Africa - Papachristou, Mariam (HAPSc Policy Briefs Series, 2021)
Within the international system, states focus on the realization of their national interests, evaluating their diplomacy, and regularly their cultural diplomacy. For instance, China exercises its cultural diplomacy, in order to promote its foreign policy’s goals. The present paper initially attempts to define the complex notion of cultural diplomacy, which is a multifactor way of promoting intercultural dialogue and augmenting states’ soft power. In particular, China’s cultural diplomacy was the most suitable case study since the Chinese state, following the Beijing’s Olympic Games, has been reintroduced in the international audience. Its reintroduction was achieved by practicing its cultural diplomacy successfully, mostly with Confucius Institutes’ function, while being dominant in the international financial system. In the case of China’s foreign policy towards Africa, Chinese cultural diplomacy was accompanied by financial diplomacy and led to a Sino-African rapprochement and to the creation of the Forum on China-Africa cooperation. It is vital though to consider if Chinese foreign policy towards the African continent is successful.